Host phylogeny constrains cross-species emergence and establishment of rabies virus in bats - Streicker, Daniel G; Turmelle, Amy S; Vonhof, Maarten J; Kuzmin, Ivan V; McCracken, Gary F; Rupprecht, Charles E (Science (American Association for the Advancement of Science), 2010)
For RNA viruses, rapid viral evolution and the biological similarity of closely related host species have been proposed as key determinants of the occurrence and long-term outcome of cross-species transmission. Using a data set of hundreds of rabies viruses sampled from 23 North American bat species, we present a general framework to quantify per capita rates of cross-species transmission and reconstruct historical patterns of viral establishment in new host species using molecular sequence data. These estimates demonstrate diminishing frequencies of both cross-species transmission and host shifts with increasing phylogenetic distance between bat species. Evolutionary constraints on viral host range indicate that host species barriers may trump the intrinsic mutability of RNA viruses in determining the fate of emerging host-virus interactions.